Antifungal susceptibility does not correlate with fungal clearance or survival in AIDS associated cryptococcal meningitis - O'Connor, L; Van Anh, D; Chau, TTH; Chau, NVV; Lan, NPH; Wolbers, M; Day, J (Oxford University Press, 2020)
We investigated the value of susceptibility testing in predicting response in AIDS-associated cryptococcal meningitis using clinical isolates from a randomized controlled trial of antifungal treatment (amphotericin monotherapy, amphotericin with flucytosine, or amphotericin with fluconazole). We found no correlation between antifungal susceptibility and either early or late survival, or fungal clearance.